EVALUATION OF ACCOUNTING INFORMATION SYSTEM (CASE STUDY OF HOTEL X SURABAYA) - Robertus Tedjobuwono (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
The development of accounting information system nowadays is very fast. The demand for transit accommodation is also increasing. This article focuses on how the development of accounting information influences the way of the accommodation services provider in generating the information for accounting purpose. The research method used is qualitative descriptive. The research categorized as qualitative descriptive as the research engaged describes the condition of the object naturally. The instruments used in the research are documents, interview, and observation. The discussion scope is limited into the accounting information system, procedures, flowchart, segregation of duties, application software, and IT infrastructure. The finding shows that there is a different between the suggested theories and the practical in the field. Efficiency and effectiveness of a system is not only handled by the procedures itself, but also the size of the company. The supervision of the owners is the key of the internal control. Moreover, the finding also shows that there is a need of improvement in accounts payable department to maintain its level of accounts payable. Keywords: Accounting, Information System, Accomodation.